Pengaruh Penambahan KOH Terhadap Kulit Kerang (Anadara granosa) Sebagai Katalis Dalam Pembuatan Biodiesel - Afandi, Trisno; Nurhayati; Awaluddin, Amir; Nainggolan, Fernando; Rahmat, Nahzim (Universitas Samudra, 2025)
The utilization of waste as a source of catalytic material in biodiesel production continues to be developed, including waste from cockle shells. In this study, the addition of KOH to the suspension of calcined cockle shells was carried out to increase the catalyst activity in biodiesel production through the transesterification reaction. The catalyst was prepared through the following stages: 1) calcination of cockle shells at 900°C for 10 hours, 2) addition of KOH to the suspension of calcined cockle shells with varying K percentages of 1%; 3%; and 5%, then the mixture was calcined at 600°C. The formed catalyst contains the minerals portlandite (Ca(OH)2) and calcite (CaCO3) based on the X-Ray Diffraction test. The addition of KOH to the suspension of calcined cockle shells was successfully carried out through the K content test using Atomic Absorption Spectroscopy. The K concentration measurement data increased along with the increase in the amount of K added, respectively at 0% K of 2381 ppm, 1% K of 2425 ppm, 3% K of 3183 ppm, and 5% K of 3800 ppm. The basicity of the catalyst was measured by titration using benzoic acid with the result of increasing basicity after the addition of KOH, each basicity of the catalyst 0% K was 1.700 mmol benzoic acid/g, 1% K was 1.700 mmol benzoic acid/g, 3% K was 1.865 mmol benzoic acid/g, and 5% K was 1.965 mmol benzoic acid/g. The catalyst activity test data in biodiesel production showed an increase in the percentage of biodiesel yield, respectively at 0% K of 56.17%, 1% K of 57.72%, 3% K of 76.33%, and 5% K of 76.85%. The catalyst activity also increased based on the measurement data of methyl ester content in biodiesel using Gas Chromatography, respectively at 0% K of 96.42%, 1% K of 97.5%, 3% K of 98.36%, and 5% K of 97.79%. The results show that the catalyst has the potential to be developed and applied in the biodiesel industry as an environmentally friendly catalytic material.